Cyclic trimers and tetramers with piperazine and 2-butyne as building blocks - Gleiter, Rolf; Hövermann, Kirstin; Rominger, Frank; Oeser, Thomas (European journal of organic chemistry, 2001)
The reaction of piperazine with 2-butyne-1,4-ditosylate in a 1:1 ratio yields the cyclic trimer 7 and the cyclic tetramer 8. 1H NMR investigations on 7 and 8 reveal a dynamic process with ΔG‡ = 13 kcal/mol. This process is attributed to an inversion of the piperazine rings. Single crystals of 7·CH3OH, 7·2 CF3COOH·H2O and 8 have been isolated and investigated by X-ray diffraction. In the first two cases methanol, or water and CF3CO2−, were included in the interior of the ring.